2007
DOI: 10.1007/s11095-006-9216-x
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Pathogenesis and Treatment of Idiopathic Pulmonary Fibrosis: A Potential Role for Stem Cells in the Lung Parenchyma and Implications for Therapy

Abstract: Idiopathic Pulmonary Fibrosis (IPF) is a chronic, progressive, and often fatal form of interstitial lung disease. It is characterized by injury with loss of lung epithelial cells and abnormal tissue repair, resulting in replacement of normal functional tissue, abnormal accumulation of fibroblasts and myofibroblasts, deposition of extracellular matrix, and distortion of lung architecture which results in respiratory failure. Despite improvements in the diagnostic approach to IPF and active research in recent ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
75
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 231 publications
1
75
0
3
Order By: Relevance
“…In contrast, we found that AGE inhibited TGF-β-induced ERK1/2 and SMAD2 phosphorylation, and increased SMAD7 expression, which was suppressed by TGF-β. TGF-β induces the alveolar EMT in human lung epithelial cells via a SMAD2-or SMAD3-dependent pathway (Yao et al, 2004;Kasai et al, 2005;Hackett et al, 2009) and is considered to be an important step toward fibroblastic foci formation in IPF (Thannickal et al, 2004;Gharaee-Kermani et al, 2007). SMAD7 inhibits TGF-β signaling through competitive binding to type 1 receptors, and it inhibits the activation of SMAD2/3 (Li et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, we found that AGE inhibited TGF-β-induced ERK1/2 and SMAD2 phosphorylation, and increased SMAD7 expression, which was suppressed by TGF-β. TGF-β induces the alveolar EMT in human lung epithelial cells via a SMAD2-or SMAD3-dependent pathway (Yao et al, 2004;Kasai et al, 2005;Hackett et al, 2009) and is considered to be an important step toward fibroblastic foci formation in IPF (Thannickal et al, 2004;Gharaee-Kermani et al, 2007). SMAD7 inhibits TGF-β signaling through competitive binding to type 1 receptors, and it inhibits the activation of SMAD2/3 (Li et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Fibrosis is analogous to abnormal wound healing occurring during tissue response due to chronic and sustained injury, microtrauma, oxidative stress, endogenous or exogenous insults, autoimmunity, and other factors. This process affects multiple organs in localized, multifocal, or disseminated forms, in conditions such as systemic sclerosis, liver cirrhosis, progressive kidney disease, cardiovascular disease, pulmonary fibroses, macular degeneration, and muscle dystrophies (Willis et al 2006, Gharaee-Kermani et al 2007, Henderson & Iredale 2007. Although chronic inflammation usually precedes fibrosis, it is neither necessary nor sufficient to trigger it, and as a result anti-inflammatory agents are usually not effective against fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Recent attention has focused on ECM components and mesenchymal cell phenotypes as being critical to the development of fibrosis (1,2). The ECM is a highly dynamic complex that varies in composition according to its tissue localization and physiologic circumstances.…”
mentioning
confidence: 99%